Poor consumers’ preferences for nutritionally enhanced foods - Wanyama, Rosina; Gödecke, Theda; Jager, Matthias; Qaim, Matin (Emerald Publishing Limited, 2019)
Purpose Micronutrient malnutrition is a public health problem in many developing countries, especially in the poorest population segments. Fortification and other food-based approaches, such as using more nutritious ingredients in processing, could help to address this problem, but little is known about poor consumers’ attitudes toward nutritionally enhanced foods. The purpose of this paper is to analyze whether poor consumers in Africa would purchase foods with more nutritious ingredients and the related willingness and ability to pay.